INTERNET OF THINGS BASED TEMPERATURE AND HUMIDITY MONITORING OF THE CALIBRATION LABORATORY ROOM AT BBSPJI KERAJINAN DAN BATIK - Zaenal Muttaqien; Dini Fakta Sari (ReTII, 2025)
This study aims to develop an Internet of Things (IoT)-based temperature and humidity monitoring system for the Calibration Laboratory of the Center for Standardization and Industrial Services for Handicrafts and Batik (BBSPJIKB). The system is designed to support environmental monitoring that requires stable temperature and humidity conditions in accordance with the SNI ISO/IEC 17025:2017 standard. The system utilizes a DHT11 sensor, NodeMCU ESP8266 microcontroller, and the Blynk application as a remote monitoring interface. Data are transmitted via Wi-Fi and displayed in real time on mobile devices. Experimental results show that the system operates stably with an average response time of 1.9 seconds, 98% connection stability, and 45% higher monitoring efficiency compared to manual methods. Therefore, IoT technology proves effective in supporting the digitalization of laboratory environmental monitoring systems efficiently and reliably.